Razvojne možnosti Vrbe - Krajner, Petra (Urbani izziv, 2007)
While preparing master plan of municipality Žirovnica, development and spatialpotential of typical Slovenian village was identified as important factor. Vrba is placed in typical highly symbolical cultural landscape of Gorenska region, it is formed as group of houses with a church as dislocated landmark. Vrba is preserved as cultural heritage where national poet was born and it is therefore protected. It represents an identity of Slovenian landscape. Vulnerability of the place is very high, but it needs to be part ofnew spatial planning and development of the municipality, the state and the European Union. Therefore new bypass road, and the house of culture is planed to be designed. By bypass road problems with the traffic in the village centerwill be solved, and some important views will be pointed. In the decision making process the public interest was censored, so as all protectionregimes were included. In suplemated plan different variants will beproceeding.
Keywords: prostorski plani; prostorski razvoj; prostorsko urejanje; razvojne možnosti; Vrba